THE RULE OF LAW, THE DOCTRINE OF LEGITIMATE EXPECTATIONS AND THE CONSTITUTIONAL COURT OF THE REPUBLIC OF CROATIA (EU and comparative law issues and challenges series (ECLIC), 2024)
An important source of the Croatian legal system is found in the Constitutional Court’s case law, which has been instrumental in shaping constitutional principles and implementing them in the proceedings of ordinary courts. Relying primarily on previously established constitutional principles, on doctrines legally binding to EU member states and their citizens, and on interpretations of EU law, legal proceedings must, above all, comply with the constitutional principle of the rule of law as one of the highest values of the constitutional order of the Republic of Croatia. All proceedings must include the requirement that legal consequences should be proportionate to legitimate expectations of parties in each individual case. Furthermore, requirements for laws stemming from the principle of the rule of law must not be such as to directly challenge the doctrine of legitimate expectation of individuals having faith in those laws and other individual legal acts. It should be noted that no legitimate expectation of exercising a certain right may arise without sufficient grounds in domestic law, separating mere “hope” and “belief” from a clear basis in a legal act or provision. Accordingly, protection of the doctrine of legitimate expectation can be viewed through the principle of procedural fairness/just proceedings guaranteed by Article 29 of the Constitution, but also as a component of ownership rights guaranteed by Article 48 thereof. The rule of law, as an essential component of every democracy, is thus also achieved through protection of the doctrine of legitimate expectation. This paper discusses the doctrine of legitimate expectation in general, as expressed by the Constitutional Court in its practice, and analyzes the most relevant Constitutional Court decisions pertaining to the protection of the doctrine of legitimate expectation within the standard of fair and just proceedings.